The nonlinear effects of banks' vulnerability to capital depletion in euro area countries - Sharada Nia Davidson; Diego Nicolas Moccero (European Central Bank (ECB), 2024)
When capital in the banking system becomes depleted, the degree to which financial intermediation and the macroeconomy are adversely affected is likely to depend on the financial and macroeconomic environment. However, existing studies either assume that the effects of bank capital shocks are linear or ignore feedback effects and the impact on the macroeconomy. Using data on the largest euro area countries and Bayesian Panel Threshold VARs, we investigate the importance of different factors in amplifying shocks in banks' vulnerability to capital depletion. Our results demonstrate that nonlinearities matter. When the banking sector is already vulnerable to large capital losses, it is more difficult for banks to accommodate a depletion in capital and lending and economic activity contract more severely. Similarly, low interest rates, which are typically associated with low bank margins and profitability, also lead to a larger decline in lending. De-risking is also more pronounced in these cases. The state of the business cycle, though, does not influence the propagation of shocks to the same extent. We conclude that financial factors play a larger role than the macroeconomic environment in heightening shocks to banks' vulnerability to capital depletion.
Keywords: C11; C33; E58; G21; 330; Bank Capital Vulnerability; Long Run Marginal Expected Shortfall; Bank Balance Sheet; Macroeconomic Adjustment; Panel Threshold VAR; Hierarchical Prior